Legal and Regulatory Evidence on Mining in Ghana Forest Reserves: A Qualitative Perspective on the Atewa Range Forest Reserve - Mensah-Odum, Nathaniel; Sarfo-Mensah, P.; Fredua-Antoh, E. (European Journal of Applied Sciences, 2025)
A global initiative to restore forest reserves in response to biodiversity loss caused by unregulated mining operations has gained significant attention, calling for the conservation of green environments, particularly forest reserves. In addressing this menace, little to no critical attention has been given to the legal and regulatory structures governing mining in forest reserves. This study critiques the Ghanaian mining regulations to identify weaknesses in the legal and regulatory framework governing mining in forest reserves, using secondary data supplemented with key informant interviews, in-depth interviews and focus group discussion data using thematic analysis. The study found that the interference by authorizing bodies/agencies through directives, lobbying, and negotiation undermines the conservation of the Atewa Forest and the attainment of global SDG agenda. The study recommends for amendment of the mining laws to clearly define "No-go zones" in forest reserves due to conservation purposes.